2013
DOI: 10.1164/rccm.201211-1981oc
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Berlin Definition for Acute Respiratory Distress Syndrome with Autopsy

Abstract: Histopathological findings were correlated to severity and duration of ARDS. Using clinical criteria the revised Berlin definition for ARDS allowed the identification of severe ARDS of more than 72 hours as a homogeneous group of patients characterized by a high proportion of DAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
296
0
18

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 370 publications
(334 citation statements)
references
References 29 publications
20
296
0
18
Order By: Relevance
“…For this reason, it is better to enroll patients who are likely to die from the disease (e.g., patients with ARDS with a low Pa O 2 /FI O 2 ratio, or high Murray score [34]), rather than simply enrolling patients with higher risk of death in general (e.g., patients with ARDS with a high Acute Physiology and Chronic Health Evaluation score). An autopsy study of patients with ARDS supports the merit of this approach: 47% of the deaths in patients with a Pa O 2 /FI O 2 ratio less than 100 were due to hypoxic respiratory failure, compared with just 11% of the deaths in the cohort overall (35).…”
Section: Clinical Trial Enrichmentmentioning
confidence: 90%
“…For this reason, it is better to enroll patients who are likely to die from the disease (e.g., patients with ARDS with a low Pa O 2 /FI O 2 ratio, or high Murray score [34]), rather than simply enrolling patients with higher risk of death in general (e.g., patients with ARDS with a high Acute Physiology and Chronic Health Evaluation score). An autopsy study of patients with ARDS supports the merit of this approach: 47% of the deaths in patients with a Pa O 2 /FI O 2 ratio less than 100 were due to hypoxic respiratory failure, compared with just 11% of the deaths in the cohort overall (35).…”
Section: Clinical Trial Enrichmentmentioning
confidence: 90%
“…Nor was lung histology included in the original BD evaluation because it is not the only pathological correlate of ARDS [3,29]; however, in a recent study using BD, diffuse alveolar damage was more frequently observed with increasing ARDS severity [30].…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies [14,15] showed that the use of non-standardized baseline PaO 2 /FiO 2 were incapable of separating patients into distinct categories of severity with significantly different mortalities. An autopsy study revealed that the Berlin criteria did not correlate with the presence of diffuse alveolar damage in more than 50 % of patients categorized as moderate and severe ARDS [16]. However, this correlation improved significantly only when patients met PaO 2 /FiO 2 criteria beyond 24 h of persistent ARDS.…”
Section: Searching For a Satisfactory Ards Definitionmentioning
confidence: 97%